Consistent response to guselkumab treatment between Hispanic and non-Hispanic patients with psoriasis: an analysis from VOYAGE 1 and VOYAGE 2. (4th July 2021) - Puig, Luis; Wu, Jashin J.; Gooderham, Melinda J.; You, Yin; Shen, Yaung-Kaung; Randazzo, Bruce; Kerdel, Francisco
Abstract: Introduction: In VOYAGE 1 (NCT02207231) and VOYAGE 2 (NCT02207244), guselkumab, an interleukin-23 blocker, was safe and effective in patients with moderate-to-severe plaque psoriasis. Methods: Patients who self-identified as Hispanic ( n  = 117) or non-Hispanic ( n  = 1686) were randomized to guselkumab, placebo, or adalimumab. Efficacy assessments included Psoriasis Area and Severity Index (PASI), Investigator's Global Assessment (IGA), and Dermatology Life Quality Index (DLQI). Results: At week 16, treatment differences for guselkumab versus placebo in the Hispanic and non-Hispanic populations were 67.4 (95% confidence interval 50.4, 84.4) and 77.2 (73.5, 80.8) percentage points for IGA 0/1 and 59.2 (41.9, 76.4) and 69.2 (65.7, 72.7) percentage points for PASI 90, respectively. Treatment differences for guselkumab versus adalimumab were 25.9 (6.5, 45.3) and 17.5 (12.8, 22.3) percentage points for IGA 0/1 and 21.4 (–0.1, 42.9) and 23.5 (18.2, 28.9) percentage points for PASI 90, respectively. Week 24 results were similar. Adverse event frequency was greater in adalimumab- versus guselkumab-treated patients in the Hispanic population only through weeks 16 and 28. In both populations, DLQI 0/1 responses were greater in guselkumab-treated versus placebo- and adalimumab-treated patients at week 16 and versus adalimumab-treated patients at week 24. Conclusions: Guselkumab safety and efficacy were consistent between Hispanic and non-Hispanic populations.